The Effectiveness of Pandan Sea (Pandanus Tectorius) Cellulose Active Charcoal in Reducing BOD, COD, TSS Level’s in Liquid Waste Tapioca - Dianti Aviliani; Fajar Indah Puspita Sari; Robby Gus Mahardika (Stannum : Jurnal Sains dan Terapan Kimia, 2022)
Tapioca liquid waste contains high organic substances and suspended solids. This research utilizes the cellulose activated charcoal of sea pandan leaves to adsorb the organic matter content and suspended solids. This study aims to determine the lignin and cellulose content of pandan sea leaves before and after delignification, determine characteristics, determine the optimum mass and optimum efficiency of tapioca wastewater adsorption. Analysis of lignin and cellulose content refers to the Chesson method with a decrease in lignin content of 11.5% to 5.4% as cellulose content increases from 65.1% to 83.6%. The results of the characteristics of water content 11.6% and ash content of 4.2%, GSA analysis showed a surface area of ​​12.6495 m2/g, a total pore volume of 0.0124607 cm3/g which included micropores and an average pore radius of 1.97015 nm. Characterization using FTIR showed cellulose functional groups such as O-H, C-H, CH2, C-O and lignin functional groups, namely aromatic CH. Adsorption was carried out with a mass variation of 1, 5 and 10 grams in 250 ml of tapioca liquid waste for 30 minutes. /L to 5.40 mg/L, TSS 875 mg/L to 9.03 mg/L and optimum efficiency at 10 gram mass with removal of COD 99.64%, BOD 99.81%, TSS 98.94%. The adsorption of cellulose activated charcoal from sea pandan leaves is superior to using microorganisms in tapioca wastewater at PT Sinar Batu Rusa Prima. Further modification is needed in the application of activated charcoal in the waste to produce a colorless filtrate.